2019
DOI: 10.1111/tid.13232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a change in cytomegalovirus prevention strategy following pediatric solid organ transplantation

Abstract: Background: An optimal cytomegalovirus (CMV) prevention strategy following solid organ transplantation (SOT) remains uncertain. This study reports on the rates of CMV events following a change in a local prevention guideline involving increased surveillance, earlier transition to oral valganciclovir, and decreased CMV-immunoglobulin use.Methods: A retrospective cohort study utilizing historical controls evaluated the rates of CMV invasive disease pre-and post-intervention among pediatric heart, liver, and kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…17 Pangonis et al reported that more CMV events occurred while patients were on prophylaxis predominantly for heart and liver transplant among 380 pediatric transplant recipients. 18 The majority of CMV DNAemia cases occurred in the first 180 days (median 126 days) post-transplant, which is comparable to other reports. However, our data are not suitable for evaluating the pre-emptive approach in our cohort.…”
Section: Outcome Of Vcg Prophylaxissupporting
confidence: 87%
See 1 more Smart Citation
“…17 Pangonis et al reported that more CMV events occurred while patients were on prophylaxis predominantly for heart and liver transplant among 380 pediatric transplant recipients. 18 The majority of CMV DNAemia cases occurred in the first 180 days (median 126 days) post-transplant, which is comparable to other reports. However, our data are not suitable for evaluating the pre-emptive approach in our cohort.…”
Section: Outcome Of Vcg Prophylaxissupporting
confidence: 87%
“…Similarly, a recent study identified that 47% of the CMV DNAemia cases occurred on appropriate VGC prophylaxis among 93 pediatric kidney transplant patients 17 . Pangonis et al reported that more CMV events occurred while patients were on prophylaxis predominantly for heart and liver transplant among 380 pediatric transplant recipients 18 …”
Section: Discussionmentioning
confidence: 96%
“…The utility of monitoring for CMV DNAemia while on antiviral prophylaxis is unclear. Pangonis et al evaluated a practice change at their institution that included increased surveillance among high‐ and medium‐risk pediatric heart, liver, and kidney transplant recipients receiving antiviral prophylaxis 16 . Increased surveillance resulted in a significant increase in the detection of CMV by PCR ( p = .04).…”
Section: Discussionmentioning
confidence: 99%
“…Increased surveillance resulted in a significant increase in the detection of CMV by PCR ( p = .04). However, most CMV events were asymptomatic DNAemia; only 3 episodes of CMV syndrome and zero cases of end‐organ disease occurred among children receiving antiviral prophylaxis 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation